FORMATION OF INTELLECTUAL CAPITAL IN THE CONTEXT OF THE INNOVATIVE ECONOMIC SYSTEM OF THE STATE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. Intellectual resources are such an important inexhaustible source that can produce new solutions to emerging political, economic, social, environmental problems. Utilization of all possibilities of state policy, interaction of state bodies with civil society structures, international organizations, application of international way out of similar crisis situations provides an opportunity to reach a secure level in this area and create preconditions for sustainable socio-economic development.The article clarifies and deepens the essence, functions and structure of intellectual capital, investigates and improves theoretical and methodological approaches to its evaluation. The analysis of the main indicators that have an impact on the level of scientific and technological security in Ukraine is carried out.The purpose of the article is to develop the theoretical and scientific-methodological bases of economic substantiation of the role of intellectual capital in forming the model of innovative national economic system.The results of scientific activity, practical experience and unfulfilled needs can be called factors of innovative opportunities. Knowledge is a manifestation of innovative opportunities available for use in business and practice. Based on the model of innovation opportunities, there are three essential components of the general knowledge required to stimulate innovation: - marketing knowledge of needs, markets and their evolution; - scientific knowledge of the structure, patterns of natural, logistical and socio-economic systems; - practical knowledge based on a generalization of previous technical, economic and social experience.Conclusion. In the Ukrainian realities in terms of integration with the European Union, such measures may include:• Enhancing the competitiveness of the research and development sector, ensuring the integration of the domestic research sector into the European Research Area.• Improving the efficiency of budget financing of the scientific sphere.• Directing domestic scientific and technical potential to meet the real needs of innovative development of the Ukrainian economy and the organization of production of high-tech goods and services.• Implementation of priority measures to improve the efficiency of the national innovation system.
Keywords: intellectual capital, intellectual potential, innovation, national economic system of the state, organizational capital, information capital